INFLUENCIA DE LA AYUDA BILATERAL EN LA RENTA PER CÁPITA DE PAÍSES DE INGRESOS MEDIOS DE AMÉRICA LATINA Y EL CARIBE, PERIODO 1980-2015 - Espinosa Sarango, Lorena Magaly (2019)
Bilateral aid from Development Assistance Committee (DAC) donors aims to promote development and social-economic welfare in underdeveloped countries. Since their creation, the Latin America and the Caribbean countries have been recipients of aid; however, their participation has been falling over time. Despite the decrease in aid volumes in the region, it is essential to analyze the effectiveness achieved by these resources, using an analytical model that describes the aggregate impact of aid on the per capita GDP of the recipient countries. In this context, the research entitled "Influence of bilateral aid on the per capita income of middle-income countries in Latin America and the Caribbean, 1980-2015 period" was carried out, whose general objective was to determine the influence of bilateral aid on the per capita GDP of countries belonging to LAC, during the period 1980-2015, by means of an econometric analysis of panel data. It was used the bibliographic, statistical, and econometrical methodology, as well as an autoregression vectors (VAR) model and an error correction (VEC) model of panel data. The results show a scenario of "aid ineffectiveness" in the region; an increase in the percentage of bilateral aid channeled to LAC countries classified by their income level in upper-middle income countries (UMIC) and lower-middle income countries (LMIC), decreases per capita GDP growth in -0.002%; -0.0007% and -0.0321%, respectively. The cointegration analysis suggests that there is a joint and simultaneous movement short and long-term between the variables and Granger's causality tests indicate that there is bidirectional causality between the variables, at the LAC and UMIC levels, except for the LMIC, which has unidirectional causality from bilateral aid flows until GDP per capita. Key words: Bilateral aid. Per capita income. Lati